Utilization of Carrot Peel as A Natural Dye Using the Maceration Extraction Method - Indah Purnamasari; Hilwatullisan; Kaisar Khadafi; Dian Purnami Handayani (Journal of Chemical Process Engineering, 2026)
Carrot peel (Daucus carota L.) is an underutilized by-product of carrot processing that is commonly discarded as household and agricultural waste, although it contains pigment-related bioactive compounds with potential application as natural colorants. This study focused on the extraction and evaluation of anthocyanin-containing pigment compounds from carrot peel using the maceration method and assessed their potential as natural dyes for textile substrates. Ethanol was selected as the extraction solvent due to its neutral character and ability to dissolve various plant pigment compounds without significantly altering the chemical stability of the extract. The maceration process was conducted using ethanol concentrations of 40% - 96%. The quality of the extract was evaluated based on absorbance, pH, yield, measured anthocyanin content, and dyeing performance on satin and calico fabrics. The results indicated that ethanol concentration influenced extract quality. Among all variations tested, the extract obtained using 96% ethanol exhibited the most favorable properties, with the highest absorbance value of 0.41075, the highest measured anthocyanin content of 61.73 mg/L, and a pH of 5.02. These results indicate that 96% ethanol produced a more concentrated pigment extract with strong color intensity and suitable acidity for natural dye applications. The dyeing tests conducted on satin and calico fabrics showed that the extract prepared with 96% ethanol produced the most visually appealing color results and received the highest preference scores from respondents.